Magnitude and Predictors of Health Care Workers Depression During the COVID-19 Pandemic: Health Facility-Based Study in Eastern Ethiopia - Yadeta, Tesfaye Assebe; Dessie, Yadeta; Balis, Bikila (Frontiers in Psychiatry, 2021)
Background: Depression of health care workers was related to work absences, resignations, and poor work performance, affecting the quality of patient care and the health care system. The Coronavirus disease pandemic has had an effect on the mental health of health care workers. Health care workers are facing challenges that can be stressful, overwhelming, and cause strong emotions, may put them at higher risk to develop depression. There is limited evidence that assesses health care workers' depression and its associated factors in the study area during the Coronavirus disease pandemic. Therefore this study aimed to assess depression and associated factors among health care workers in eastern Ethiopia. Method: The cross-sectional study design was conducted from October 26th to November 15, 2020. A total of 265 health care workers from 10 health facilities participated. Patient Health Questionnaire was used for the collection of depressive symptoms. The data were analyzed by using STATA version 14 software. To assess the association between depression and the predictors Adjusted Odds Ratio along with a 95% confidence interval was estimated by using logistic regression analysis. A statistical significance was declared at p-value ≤ 0.05. Results: Of the total 265 study participant, 176 (66.4%) and 95% CI: 60.4%, 71.8% of them reported depressive symptoms. Of 176 reported symptoms of depression 27.9, 24.1, 9.4, 3.7, and 1.1% were had minimal, mild, moderate, moderate-severe, and severe depressive symptoms respectively. The multivariable logistic regression analysis revealed the odds of depression were 2.34 times higher among female participants compared to male participants (AOR: 2.34, 95%CI: 1.09-5.02). In addition, the odds of depression for participants who perceived susceptibility to COVID-19 was 4.05 times higher among their counterpart (AOR: 4.05, 95%CI: 1.12-14.53). Conclusions: Health care workers who experienced depression in the study was high. Health care workers' mental health needs to be protected during the COVID-19 pandemic. Female health care workers and health care workers perceived susceptibility of COVID-19 need attention.